OrnaVerum
v 6.30.00
28 Jan 2022
updated 28 Jan 2022

Eqn 11d Help

Suppose that p = exp (logeq) = e(raised to the power of logeq)

This would be a typographical nightmare … but there's a much simpler way of looking at it: the equation is telling us that the logarithm of p to the base e is logeq

logep = logeq

and in even simpler terms

p = q

So if we exponentiate both sides of x/a = loge {u + √(1+u2)}, we get

exp(x/a) = exp (loge {u + √(1+u2)})

which immediately simplifies to

ex/a = u + √(1+u2)